Augmented reality (AR) technology on the android operating system in human respiratory system: From organ to cell - Daniar Setyo Rini; Eka Putri Azrai; Ade Suryanda; Shabrina Syifa Inayah; Anindya Annisa Khansa; Mathias Bagas Kurnianto (Biosfer: Jurnal Pendidikan Biologi, 2022)
Understanding the object of learning material that is abstract is currently still an obstacle faced by students. The use of technology in learning is expected to reduce the obstacles faced by these students. Augmented reality (AR) is a technology that is currently being widely applied in the learning process because it is considered capable of helping students understand abstract learning materials with 3D object features. This study aims to design and develop AR, especially in the anatomical structure of organs in the human respiratory system, which is then integrated into biological practice in the laboratory. The AR application has been designed, created, validated, and published under AR Synapse (Augmented Reality Respiratory System). The AR application developed is based on the android system and has gone through validation tests by experts. Five expert validators who work as lecturers and high school teachers. Expert validation results with an average score of 3.6 from a maximum score of 4.0, which states that the AR Sinaps application is 91.2%, has functioned well, supports learning, provides objects relevant to teaching materials, and is considered to increase students' learning motivation. Furthermore, it has good prospects for continuous development. Students' satisfaction survey and user evaluation also gave a good response with an average rating percentage of 85.1%.